Healing Chamber for Grafted Vegetable Seedlings in Florida - Monica Ozores-Hampton; Aline Coelho Frasca (EDIS)
Grafting is a horticultural technology that combines two plants, the scion and the rootsock, to create a plant with desirable features from both parts. In the United States, the use of vegetable grafting in field production remains limited, although 70% of the total hydroponic greenhouse tomato area uses grafted seedlings. Large, commercial grafting operations use controlled-environment growth chambers, but the high cost limits their use in most small-scale grafting operations. Healing chambers are an alternative solution that provides proper healing at a lower cost for growers and researchers. This 5-page fact sheet was written by Monica Ozores-Hampton and Aline Coelho Frasca, and published by the UF Department of Horticultural Sciences, October 2013.